Parental stress in families of children with special educational needs: a systematic review - Cheng, Andrew W. Y.; Lai, Cynthia Y. Y. (Frontiers in Psychiatry, 2023)
This systematic review aimed to identify the risk factors and protective factors for parental stress in families with children with special educational needs. Studies have indicated that the well-being of families is related to the physical, psychological, and social conditions of the children, and also the family functioning, stress coping strategy, social and professional support of their parents. The parents of children with special educational needs experience high levels of parental stress. Identifying the associated risk factors and protective factors may shed light on the provision of social and psychological interventions to promote the mental well-being of these parents. Boolean operators were used to search multiple online databases, and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines were applied in this systematic review. Data were extracted into categories of population, age, region, the child's diagnosis, the stress-measuring instrument, and the risk factors and protective factors. Twenty-six studies including 5,169 parents and 3,726 children were reviewed. The following four major risk factors and protective factors were found to be associated with parental stress: the sex of the parents, diagnosis-related coping issues, socioeconomic characteristics, and social isolation of the parents. This systematic review identified four significant risk factors and protective factors related to social support from couples, family members, and social circles. Various agencies may provide financial and manpower assistance and professional support and services to improve the parents' knowledge and coping skills, as well as affectional support and early screening and continuous assessment of the parents' progress. Social policies and interventions offering continuous and diagnosis-related support to the parents of children with special educational needs are highly recommended.